Mapping the human T cell repertoire to recurrent driver mutations in MYD88 and EZH2 in lymphoma. (3rd July 2017) - Nielsen, Julie S.; Chang, Andrew R.; Wick, Darin A.; Sedgwick, Colin G.; Zong, Zusheng; Mungall, Andrew J.; Martin, Spencer D.; Kinloch, Natalie N.; Ott-Langer, Susann; Brumme, Zabrina L.; Treon, Steven P.; Connors, Joseph M.; et al.
ABSTRACT: Oncogenic "driver" mutations are theoretically attractive targets for the immunotherapy of lymphoid cancers, yet the proportion that can be recognized by T cells remains poorly defined. To address this issue without any confounding effects of the patient's immune system, we assessed T cells from 19 healthy donors for recognition of three common driver mutations in lymphoma: MYD88 L265P, EZH2 Y641F, and EZH2 Y641N . Donors collectively expressed the 10 most prevalent HLA class I alleles, including HLA-A*02:01. Peripheral blood T cells were primed with peptide-loaded dendritic cells (DC), and reactive T cells were assessed for recognition of naturally processed mutant versus wild type full-length proteins. After screening three driver mutations across 17–26 HLA class I alleles and 3 × 10 6 −3 × 10 7 T cells per donor, we identified CD4 + T cells against EFISEN CGEII from EZH2 Y641N (presented by HLA-DRB1*13:02) and CD8 + T cells against RP IPIKYKA from MYD88 L265P (presented by HLA-B*07:02). We failed to detect RP IPIKYKA-specific T cells in seven other HLA-B*07:02-positive donors, including two lymphoma patients. Thus, healthy donors harbor T cells specific for common driver mutations in lymphoma. However, such responses appear to be rare due to the combined limitations of antigen processing, HLA restriction, and T cell repertoire size, highlighting the need for highly individualized approaches for selecting targets.